The future pharmacy is key to better health for me and the NHS: a patient's personal view - Marlene Winfield, OBE (Future Healthcare Journal)
This article is a patient view of how the future pharmacy could play a key role in devolving routine care for minor ailments and management of long-term conditions. As someone with three long-term conditions, I see an expanded role for pharmacies in supporting me to manage them effectively, filling a major gap: someone to see me and my medications regimen as a whole. A comprehensive national future pharmacies transformation programme is key to NHS sustainability. It must be fully funded, well planned and well executed.